الانتهاكات الجسيمة لقواعد القانون الدولي الإنساني: بين نص المادة 8/2 من النظام الأساسي للمحكمة الجنائية الدولية ومعوقات تفعيلها - لونيسي, علي (University of Eloued جامعة الوادي, 2019)
يعد فرض قواعد المسؤولية الجنائية الدولية على حالات الانتهاكات الجسيمة لقواعد القانون الدولي الانساني في الواقع جزءا أساسيا من النظام القانوني الدولي الجنائي حيث تتوقف فاعليته على مدى توافر الضمانات القانونية الدولية الموضوعية والإجرائية التي تؤسس لمبدأ عدم الافلات من العقاب. لذلك فقد أعتبر انشاء المحكمة الجنائية الدولية أحد أهم مظاهر سعي المجتمع الدولي الى تكريس العدالة الجنائية الدولية والتي يتم بإعمالها اقرار أوجه تنفيذ المسؤولية الجنائية الدولية عن الانتهاكات الجسيمة لقواعد القانون الدولي الانساني، من حيث هي أداة فعالة لتكريس الزامية القانون الدولي الانساني ذاته. وعليه فان دراسة العلاقة بين القانون الدولي الإنساني والمحكمة الجنائية الدولية تنطلق من النظر الى أن عملية انشاء هذه المحكمة كانت لضرورة سد نقص في النظام القانوني الجنائي الدولي عامة، والقانون الدولي الإنساني خاصة. The imposition of rules of international criminal responsibility for cases of gross violations of the rules of international humanitarian law is in fact an integral part of the international criminal law system, the effectiveness of which depends on the availability of international substantive and procedural legal guarantees that establish the principle of non-impunity. Therefore, the establishment of the International Criminal Court was considered one of the most important manifestations of the international community's endeavor to establish international criminal justice, which is to implement the implementation of international criminal responsibility for serious violations of the rules of international humanitarian law because it is an effective instrument to enforce the obligation of international humanitarian law itself. Thus, the study of the relationship between international humanitarian law and the International Criminal Court comes from the view that the process of establishing such a court was a necessity to fill a gap in the international criminal law system in general and international humanitarian law in particular.
مجلد3، عدد2
Keywords: القانون الدولي الإنساني، المحكمة الجنائية الدولية، مبد أعدم الإفلات من العقاب، الانتهاكات الجسيمة.; International Humanitarian Law, International Criminal Court, the principle of non-impunity, Gross Violations